Identifying postoperative atrial fibrillation in cardiac surgical patients posthospital discharge, using iPhone ECG: a study protocol. Issue 1 (13th January 2015) - Lowres, Nicole; Freedman, S Ben; Gallagher, Robyn; Kirkness, Ann; Marshman, David; Orchard, Jessica; Neubeck, Lis
Abstract : Introduction: Postoperative atrial fibrillation (AF) occurs in 30–40% of patients after cardiac surgery. Identification of recurrent postoperative AF is required to initiate evidence-based management to reduce the risk of subsequent stroke. However, as AF is often asymptomatic, recurrences may not be detected after discharge. This study determines feasibility and impact of a self-surveillance programme to identify recurrence of postoperative AF in the month of posthospital discharge. Methods and analysis: This is a feasibility study, using a cross-sectional study design, of self-screening for AF using a hand-held single-lead iPhone electrocardiograph device (iECG). Participants will be recruited from the cardiothoracic surgery wards of the Royal North Shore Hospital and North Shore Private Hospital, Sydney, Australia. Cardiac surgery patients admitted in sinus rhythm and experiencing a transient episode of postoperative AF will be eligible for recruitment. Participants will be taught to take daily ECG recordings for 1 month posthospital discharge using the iECG and will be provided education regarding AF, including symptoms and health risks. The primary outcome is the feasibility of patient self-monitoring for AF recurrence using an iECG. Secondary outcomes include proportion of patients identified with recurrent AF; estimation of stroke risk and patient knowledge. Process outcomes and qualitative data related to acceptability of patient's use of the iECG and sustainability of the screening programme beyond the trial setting will also be collected. Ethics and dissemination: Primary ethics approval was received on 25 February 2014 from Northern Sydney Local Health District Human Resource Ethics Committee, and on 17 July 2014 from North Shore Private Hospital Ethics Committee. Results will be disseminated via forums including, but not limited to, peer-reviewed publications and presentation at national and international conferences. Trial registration number: ACTRN12614000383662.